2014
DOI: 10.1590/0104-1428.1663
|View full text |Cite
|
Sign up to set email alerts
|

Síntesis de hidrogeles de acrilamida en soluciones acuosas de etanol

Abstract: Resumen: En el presente trabajo se realizó la polimerización de acrilamida en soluciones acuosas de etanol, variando la composición del etanol en la solución; obteniéndose tanto nanogeles como macrogeles. Se determinó la capacidad de absorber agua de los macrogeles; obteniéndose materiales que tienen una capacidad de absorber desde 40 y hasta 90 gramos de agua por gramo de xerogel y el tamaño de partícula de los nanogeles fueron desde 71 nm y hasta 463 nm.Palabras clave: Acrilamida, etanol, nanoparticulas. Pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…In a similar study carried out by Rathna and Damodaran [9] with fish modified hydrolysates, it was shown that the modified isolates treated with ethanol had increased capacity of water-uptake of approximately 50% when compared with those without treatment with ethanol. According to García Sánchez and Cortés Ortega [16] , the aqueous solution with ethanol stabilizes growing particles, running as the continuous phase, a system similar to emulsion or microemulsion, depending on the amount of ethanol in the reaction mixture. It is interesting to point out that the protein isolate used did not have any fat residual.…”
Section: Kinetics Of Water-uptakementioning
confidence: 99%
See 2 more Smart Citations
“…In a similar study carried out by Rathna and Damodaran [9] with fish modified hydrolysates, it was shown that the modified isolates treated with ethanol had increased capacity of water-uptake of approximately 50% when compared with those without treatment with ethanol. According to García Sánchez and Cortés Ortega [16] , the aqueous solution with ethanol stabilizes growing particles, running as the continuous phase, a system similar to emulsion or microemulsion, depending on the amount of ethanol in the reaction mixture. It is interesting to point out that the protein isolate used did not have any fat residual.…”
Section: Kinetics Of Water-uptakementioning
confidence: 99%
“…This increase in swelling capacity of gels at pH 10, according to Hwang and Damodaran [27] , is associated with electrostatic repulsion force which is directly proportional to the square charge of molecular network, thus, even though there is a small increase in the charge of the network due to ionization of tyrosine residues (pK 3 = 9.6) there will be an increase in electrostatic repulsion inside the network of the gel, resulting in an increase of gel expansion and water retention. Other authors [16] state that growing particles are surrounded by layers of aqueous ethanol solution, which allow the stability of the particles growing in establishing a colloidal system.…”
Section: Effect Of Ph Over Water-uptake Capacitymentioning
confidence: 99%
See 1 more Smart Citation
“…When polymeric gels are not filled with fluids, they are dubbed xerogels [14] . This class of polymeric material has many applications, such as in tissue engineering, drug delivery, prosthetics and membranes applied in separation processes [14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…Various efforts have been made to characterize polymeric gels through TD-NMR [15,[17][18][19][20][21][22] , but the majority of the reported methods involve soaking the sample in a solvent [14,19,23,24] , with the analysis being conducted under strict temperature conditions [18,20,21] , or limiting the chemical nature of the polymeric matrix to elastomers [6,12,[18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%